Measurements of Higgs boson production and couplings in diboson final states with the ATLAS detector at the LHC - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2013)
Measurements are presented of production properties and couplings of the recently discovered Higgs boson using the decays into boson pairs, H→γγ, H→ZZ*→4ℓ and H→WW*→ℓνℓν. The results are based on the complete pp collision data sample recorded by the ATLAS experiment at the CERN Large Hadron Collider at centre-of-mass energies of s=7 TeV and s=8 TeV, corresponding to an integrated luminosity of about 25 fb-1. Evidence for Higgs boson production through vector-boson fusion is reported. Results of combined fits probing Higgs boson couplings to fermions and bosons, as well as anomalous contributions to loop-induced production and decay modes, are presented. All measurements are consistent with expectations for the Standard Model Higgs boson. © 2013 CERN.